Coexistence in Islamic Sharia: A Study of Social Interaction Majority and Minority in Aceh - Fariza, Muhammad Rio (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
This study examines the social interaction between the majority of Muslims and non-Muslim minorities in Aceh in the context of the implementation of Islamic Sharia. Using qualitative methods and case study approaches, this study explores how both groups build social harmony through cultural adaptation, participation in social activities, and inclusive attitudes of the majority. The results showed that non-Muslim minorities actively studied local culture and followed the customs of the majority community to facilitate interaction and avoid conflict. Meanwhile, the majority of Muslims show a moderate attitude by giving space for minorities to practice their beliefs without coercion. This mutual respect reflects religious tolerance and moderation, which is the basis of Aceh's social harmony. These findings show that diversity can be managed well through dialogue, mutual respect, and inclusive policies. This study contributes to understanding the majority-minority relationship in societies that apply Islamic law and how to create social cohesion amid differences.